Electrical performance and reliability characterization of a SiC MOSFET power module with embedded decoupling capacitors - Yang, Li; Li, Ke; Dai, Jingru; Corfield, Martin; Harris, Anne; Paciura, Krzysztof; O'Brien, John; Johnson, C. Mark (Institute of Electrical and Electronics Engineers, 2018)
Integration of decoupling capacitors in SiC MOSFET modules is an advanced solution to mitigate the effect of parasitic inductance induced by module assembly interconnects. In this paper, the switching transient behavior is reported for a 1.2kV SiC MOSFET module with embedded DC-link capacitors. It shows faster switching transition and less overshoot voltage compared to a module using an identical package but without capacitors. Active power cycling and passive temperature cycling are carried out for package reliability characterization and comparisons are made with commercial Si and SiC power modules. Scanning acoustic microscopy images and thermal structure functions are presented to quantify the effects of package degradation. The results demonstrate that the SiC modules with embedded capacitors have similar reliability performance to commercial modules and that the reliability is not adversely affected by the presence of the decoupling capacitors.